Monitoring the Oceanic Waters of the Canary Islands: the deep hydrographic section of the Canaries - Vélez-Belchí, Pedro; Hernández-Guerra, Alonso; Barrera, C.; Fraile-Nuez, Eugenio; Barrera, A.; Llinás, O.; Benítez-Barrios, Verónica María; Domínguez, F.; Alonso-González, I.; González Dávila, M.; Santana-Casiano, Juana MagdalenaM; Hernández-Brito, J.J.; et al. (2014)
Due to the high density and heat capacity of water, the ocean modulates climate in scales much larger than the atmosphere, both spatially and temporally. In order to understand the mechanisms governing this internal variability of the ocean, and therefore climate, it is necessary to have long systematic observations. The Atlantic Meridional Overturning Circulation (AMOC), which is composed by the south- north circulation, transports 18Sv (1Sv=10E6m3/s) of water that carries more that 1.5PW (1PW=10E15W) of heat to the North Atlantic, and therefore plays a determining role in regulating the climate in Europe. An important component of the AMOC is the subtropical gyre, the largest oceanic structure of the North Atlantic. The Canary Islands are immersed in the eastern margin of the subtropical gyre, in the coastal transition zone of the Canary Current Upwelling System and therefore they are an ideal place for the study of the subtropical gyre variability. With this background, in 2006 the Spanish Institute of Oceanography began (IEO) the program deep hydrographic section around the Canary Islands (Raprocan), in order to establish the scales of variability in the range decadal/subdecadal in the subtropical gyre, specifically in its eastern margin. Based on previous results the observational strategy of Raprocan consists in hydrographic cruises in two seasons, with 50 hydrographic stations around the Canary archipelago. In each one of the stations velocity, temperature, salinity, pressure, oxygen, turbidity and fluorescence is continuously measured ( CTD ). In each station 24 samples are taken for calibration of the above variables as well as for determination of alkalinity, carbon content and chlorophyll. This program is carried out in collaboration with the University of Las Palmas de Gran Canaria (ULPGC) and with the Oceanic Platform of the Canary Islands (PLOCAN) that provides glider data since 2013. The warming of the upper 600 m continues at a rate of 0.14 ° C/ decade in the oceanic waters and 0.32 ° C / decade ...